Problematika Bahasa Al-Qur'an sebagai Tantangan Worldview Islam - Hunaida El 'Abidah; Rizkyana Wahyu Laras Pertiwi; Nur Rohmatul Mufidah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
The aim of this research is revealed the problems of the Qur’an as a challenge to the Islamic worldview. At present the attacks that are present for Muslims are of very various form. Starting from ideological attack and all aspect of human life. Qur’an as a guide for Muslims throughout the word has become the main target of western scholars in their effort to tear down Islamic structures. One of the efforts is to confuse Muslims with the Qur’an. Manifestation of this effort is to make Qur’an appear to have problems including: 1) Qur’an as text, 2) Qur’an as a cultural product, 3) Humanistic problem in text, 4) Problem textually Qur’an. This problem poses as a challenge to the Islamic worldviews. For this reason, the author tries to reveal the Islamic worldviews of the Qur’an by studying literacy. The result of the concept of error which is used as blasphemy for the sacredness of the Qur’an is not true. All of this has a basis based on the Islamic worldviews. If the foundation of a person’s worldviews is strong then the building above it will also be strong. On the other hand, if there is no footing, the building will collapse. This discussion uses literature studies by collecting library data, reading and, recording and processing research materials.